IMPLEMENTASI UNDANG-UNDANG NOMOR 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN TERKAIT PEMBERANTASAN KORUPSI - Mirza Sahputra; Husniati (Puslatbang KHAN, 2021)
Based on the report from Corruption Eradication Commission, notes that since 2014 to 2019 there were 34 members of the DPR and DPRD, 164 Ministry Officials and Institutions, 39 BUMN and BUMD officials, 75 Provincial Government Officials and 227 Officials of District and city governments involved in corruption and abuse of authority cases. Therefore, the Government form the Law No. 30 Year 2014 on Government Administration is to ensure government agencies/officials use their authority in accordance with the provisions applied. This study resulted in several conclusions, including the minimum implementation of the Law of Government Administration as the main reference for agencies and/or government officials in efforts to improve the quality of government administration. Lack of understanding, commitment and the role of each stakeholder, have several implications for the minimum contribution of UUAP as an instrument for preventing criminal acts of corruption and in handling abuse of power cases.